Maternal Postnatal Psychopathology Predicts Identity Diffusion in Young Adult Offspring - Jens Joas; Justine Hussong; Sena Aktürk; Kirstin Goth; Eva Möhler; Hannah Honecker-Gebauer (Children)
Background/Objectives: In the new conceptualization of personality disorders (PD) in ICD-11 and Diagnostic and Statistical Manual 5 Alternative Model of Personality Disorders (DSM-5 AMPD), identity development in terms of impaired personality functioning plays a central role in diagnostic guidelines and determining PD severity. On the one hand, there is a temporary identity crisis while keeping an integrated sense of identity and, on the other hand, there is pathological identity diffusion, which is associated with a high risk of a current or emerging PD. The latter is characteristic not only of borderline PD but of all personality disorders and should be detected as early as possible to prevent chronic illness and critical life courses. Maternal psychopathology is linked to several areas of child psychopathology (e.g., eating disorders, depression). In the current study, its potential to predict a child’s impaired identity development is investigated. Methods: A total of 101 mothers were asked about their health status 2 weeks after the birth of their child and when their child was 6 weeks, 4 months, 14 months and 5.5 years of age. Specifically, physical and psychological symptoms were assessed with SCL-90-R. In addition, their children were assessed in young adulthood regarding their identity development with the AIDA (Assessment of Identity Development in Adolescence) questionnaire. Linear regression models were used to investigate the amount of explanation of children’s identity diffusion by maternal symptom burden. Results: Maternal psychopathology significantly predicted identity diffusion at all time points with small effect sizes, while after 14 months, the explanation model showed a medium effect size. Conclusions: The present data suggest a relevant influence of maternal psychopathological symptoms on their children’s identity development in terms of functioning that has not yet been empirically shown in a longitudinal study. This finding highlights the importance of including further factors (particularly on the part of the child) in longitudinal studies and of investigating this clinically highly relevant relationship in greater depth.